BRI is an independent predictor of new-onset kidney stones in a non-diabetic population: a retrospective analysis - Fan, Xiaohong; Yu, Si; Li, Jing; Lin, Songbai; Ai, Sanxi; Wu, Haiting; Fei, Yunyun; Qin, Yan; Chen, Gang; Li, Xuemei (Frontiers in Endocrinology, 2025)
BackgroundKidney stones are a prevalent global health concern with significant morbidity and costs. The body roundness index (BRI), reflecting central fat distribution, might offer improved risk assessment than traditional predictors like body mass index (BMI). This study aimed to determine whether BRI is an independent predictor of new-onset kidney stones in a Chinese cohort and to compare its predictive utility with that of BMI.MethodsA retrospective cohort analysis was conducted using data from 510,778 physical examinations at Peking Union Medical College Hospital from 1994 to 2024. After exclusions, 26,594 individuals with follow-up exceeding five years were included. Demographic, anthropometric, and laboratory data were collected. Cox proportional hazard models were used to assess the associations between BMI/BRI and kidney stone risk, adjusting for confounders. Stratified analyses were performed by diabetes status.ResultsAmong 26,594 participants (mean age 41.2 ± 12.6 years, 50.2% male), 462 developed new-onset kidney stones during follow-up. Individuals with new-onset kidney stones had significantly higher BRI (3.52 vs 3.15, p<0.01), BMI (24.64 vs 23.74 kg/m2, p<0.01), and prevalence of metabolic abnormalities (e.g., hypertension, dyslipidemia, hyperuricemia, impaired glucose metabolism; all p<0.01). In unadjusted analysis, both BMI (HR 1.07, 95% CI 1.04-1.09) and BRI (HR 1.29, 95% CI 1.21-1.37) predicted kidney stones. After full adjustment for metabolic confounders, only BRI remained significantly associated with stone risk (adjusted HR 1.13, 95% CI 1.02-1.26), while BMI did not (p=0.86). Stratified analysis revealed that BRI’s predictive value was substantial only in non-diabetic individuals (adjusted HR: 1.17, 95% CI: 1.06–1.30), with no association observed in participants with diabetes (p > 0.05).ConclusionBRI, but not BMI, is an independent predictor of new-onset kidney stones in non-diabetic individuals. These findings highlight the importance of visceral adiposity in kidney stone pathogenesis and suggest BRI’s potential utility in risk stratification and preventive strategies.